REVIEW PAPERPathology of the cervical spine in rheumatoid arthritis - Raczkiewicz-Papierska, Anna; Bachta, Artur; Zagrodzka, Magdalena (Reumatologia/Rheumatology, 2005)
Infammatory changes of the cervical spine are reported in 25-80% of patients with rheumatoid arthritis. Atlanto-axial instability is the most common form of cervical involvement. The risk factors are: high disease activity, duration of the disease, early disease onset, seropositivity. Myelopathy is rare but when present portends a poor prognosis. Early surgical intervention prevents development of myelopathy and improves outcome in that group of patients.